Problems of implementation by insurers of the right of recourse to the person who caused the damage - Bayan, M.; Ospanova, D.A.; Ploczkaya, O.A. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
The authors of this article analyze the current legislation in the field of civil liability insurance of vehicle owners in terms of the use of the insurers’ right of recourse to the person who caused the damage. Article 28 of the Law “On Compulsory Insurance of Civil Liability of Vehicle Owners” dated July 1, 2003 regulates the recovery of insurance payment by way of recourse (regress claims). Analysis of the practice of implementation by insurers of this right in court has revealed some shortcomings and imperfections of the Article 28 of the Law under consideration. As a result, the authors of the article offer recommendations for improving the rules governing the relations associated with the implementation by insurers of their right of recourse to the insured (insured). The introduction of the institution of compulsory insurance of civil liability of vehicle owners has significantly reduced the burden on the judicial system in terms of disputes on recovery of damage caused as a result of a traffic accident. However, in the judicial practice on this type of insurance, many questions arise. The recommendations in the article are based on the results of court disputes involving the author of the article.